Analysis of the Influence of Indian Culture on Parenting Patterns and Child Development in Madras Village, Medan - Sidauruk, Putri Indah Sari; Manurung, Elsa Sofhiray; Utami, Adinda Tri; Purba, Dianita Cristiani (Lembaga Riset Mutiara Akbar, 2024)
This study aims to examine the influence of Indian culture in Kampung Madras on parenting styles and its impact on child development. The study analyzes how the values and traditions of Indian culture, applied in daily life, affect parenting methods. The research employs a qualitative method, with data collection techniques through observation, interviews, and documentation. The subject of the study is a mother from the community residing in Kampung Madras, India. The study analyzes how the values and traditions of Indian culture, applied in daily life, influence parenting methods. The community in this area shares similar traditions with the general population; parenting in India is greatly influenced by the culture of living together in extended families (mitakshara), where interdependence among families living in the same household is very strong. From an early age, Indian parents teach children about kinship positions, gender roles, and birth order.).